Hubungan antara Motivasi Belajar dan Kemampuan Analisis Fisika Siswa SMA Ditinjau dari Perspektif Gender - Nurajijah, Siti; Irvani, Asep Irvan; Muhajir, Siti Nurdianti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study focuses on evaluating the correlation between learning motivation and students’ analytical ability in physics, as well as comparing these two variables from a gender perspective. Using a quantitative approach with a correlational–comparative research design, the study involved 50 students of grade XII MIA (8 male students and 42 female students). The results indicate that: (1) there is a very strong and significant correlation between learning motivation and students’ analytical ability in physics learning (r = 0.935; Sig. 0.000 < 0.05); and (2) there is no significant difference in either analytical ability or learning motivation between male and female students. It can be concluded that learning motivation is a key factor influencing students’ success in physics analysis, regardless of gender differences.